General and Digital Job Demands and Occupational Burnout: Understanding the Role of Personal and Organizational Resources - Kamandulytė, Raminta (Psichologija, 2025)
The aim of this study is to assess the relationship between general job demands and digital job demands and occupational burnout and to identify protective factors for occupational burnout at work. The study involved 278 participants. All participants were actively employed. All participants completed a questionnaire consisting of items related to occupational burnout, quantitative job demands, qualitative job demands, technological overload, dependence on technology at work, communication overload, information overload, increasing learning needs, mastery at work, self-efficacy in adapting to technological progress, managerial support, and promotion of information literacy in the organization. The results showed that quantitative job demands, technological overload at work, and information overload at work predict occupational burnout at work. Finally, the results show that personal organizational resources do not moderate the association of occupational burnout with general and digital job demands, but personal and organizational resources negatively predict occupational burnout. The added value of this study for organizations is that it will enable them to encourage organizations to help employees develop personal resources, such as self-efficacy, to adapt to technological progress at work and job crafting, as well as to encourage organizations to focus on promoting managerial support for employees and information literacy training in the organization, which may reduce occupational burnout at work. Moreover, this study will allow organizations to pay attention to quantitative job demands, technological overload at work, and information overload at work as they can predict burnout at work.
Keywords: occupational burnout; general job demands; digital job demands; self-efficacy to adapt to technological progress at work; job crafting